Response of eight storey regular and irregular buildings with transfer beam under near field earthquake excitation with vertical component - Doreen Bong Yin Yin (School of Environmental Engineering, University Malaysia Perlis, 2014)
In this paper the effect of the vertical component of ground motion on the response of reinforced concrete frame is investigated and their performances of the analyses are expressed in term of interstorey drift ratio and axial variation. The present work assesses the earthquake response of four reinforced concrete planar frames which subjected to ten single ground motions with vertical component analysed by nonlinear time history analysis using RUAUMOKO.